Atmospheric models for artificial satellites orbit determination – a review - Giacaglia, Giorgio Eugenio Oscare; Marcondes, Alex Oliveira (Revista Ciências Exatas, 2008)
In this work we present a review of the most important models of the atmospheric density, as necessary for a precise evaluation of the aerodynamic forces acting on an artificial satellite of the Earth at altitudes above 50 km. All available modes in the literature are briefly described. Jacchia´s Model taking into account successive contributions by Harris, Priester e Roberts is developed in details. The development of Brazilian spacecrafts today and in near future and their orbital estimation and control justify this development.